Historical Anatomical Collections of Human Remains: Exploring Their Reinterpretation as Representations of Racial Violence. (March 2021) - Zuckerman, Molly K.; Austin, Rita M.; Hofman, Courtney A.
We synthesize how the tools of molecular anthropology, integrated with analyses of skeletal material, can provide direct insights into the context-specific experiences of racial structural violence in the past. Our work—which is emblematic of how biological anthropologists are increasingly interested in exploring the embodied effects of structural and race-based violence—reveals how anthropology can illuminate past lived experiences that are otherwise invisible or inscrutable. This kind of integrative research is exposing the legacies of structural violence in producing anatomical collections and the embodied effects of structural violence evident within individuals in those collections.